Performance Evaluation of 3.5 kVA Hybrid Inverter Following Standard Engineering Practices and Safety Procedures - ADEOGO, Johnson O.; OLALUYI, Olawale J.; OJO, Olumuyiwa A.; AYODELE, Abayomi T.; OLAJUYIN, Elijah A.; BELLO, Fasasi; OFODU, Paul C. (FUDMA Journal of Engineering and Technology, 2026)
The global energy landscape has undergone a significant transformation in recent decades, with renewable energy technologies gaining prominence as alternatives to fossil fuel-based power generation. This shift is driven by the dual challenges of meeting rising electricity demand and mitigating the environmental consequences of greenhouse gas emissions. This study deals with assessment of different types of solar inverters. The purpose of this study is to carry out the performance evaluation of 3.5 kVA Hybrid Inverter following standard engineering practices and safety procedures. To reduce distortion content, filters are designed which in turn improves the power factor and efficiency of the system. Several pulse width modulation performances were used to reduce the percentage of harmonic distortion within IEEE standards. The simulation of the system was evaluated using Excell Software. The output waveforms of percentage harmonic distortion were obtained using Qualister Analyzer (CA 8338). The inverter performs the differing function of a rectifier, which converts DC to AC in different forms. The results show that the projected hybrid inverter can reduce the total power distortion under linear loading environments. A design experiment is presented for a 3.5 kVA, 50Hz power inverter under different load settings to authenticate the study.
Keywords: Engineering Practice, Evaluation, Hybrid Inverter, Performance, Safety.